Răspuns :
10-10:{1+3•[(57-60:4•2):3+21]:10}=
10-10:{1+3•[(57-15•2):3+21]:10}=
10-10:{1+3•[(57-30):3+21]:10}=
10-10:{1+3•[27:3+21]:10}=
10-10:{1+3•[9+21]:10}=
10-10:{1+3•30:10}=
10-10:{1+3•3}=
10-10:{1+9}=
10-10:10
10-1=9
Salutare!
[tex]\bf 10-10:[1+3\cdot[(57-60:4\cdot2):3+21]:10]=[/tex]
[tex]\bf 10-10:[1+3\cdot[(57-15\cdot2):3+21]:10]=[/tex]
[tex]\bf 10-10:{1+3\cdot[(57-30):3+21]:10}=[/tex]
[tex]\bf 10-10:[1+3\cdot(27:3+21):10]=[/tex]
[tex]\bf 10-10:[1+3\cdot(9+21):10]=[/tex]
[tex]\bf 10-10:(1+3\cdot 30:10)=[/tex]
[tex]\bf 10-10:(1+90:10)=[/tex]
[tex]\bf 10-10:(1+9)=[/tex]
[tex]\bf 10-1=[/tex]
[tex]\boxed{\bf 9}[/tex]
==pav38==